Identifying Pronunciation Errors Using English Speaking Management Methods in Tourism-Based Schools - Linerda Tulaktondok; Rachel; Yizrel Nani Sallata; Amelisa Nugraha Padaunan; Aprisel Bimbang Duapadang (Universitas Sulawesi Barat, 2026)
This study aims to identify common pronunciation errors among students in tourism-based schools in Toraja, Indonesia, and assess the potential application of English Speaking Management (ESM) methods as a structured approach to improve pronunciation. With the growing importance of English proficiency in the tourism sector, especially in regions like Toraja, improving pronunciation is crucial for enhancing communication with international visitors. Using a qualitative-collaborative research approach, data were collected through Focus Group Discussions (FGD) with 15 teachers and 30 students. The study revealed that phonemic errors, stress misplacement, and difficulties with consonant clusters were prevalent among students. The implementation of ESM methods, including drilling, role play, and technology integration, showed significant improvements in pronunciation accuracy and students’ speaking confidence. The findings support the potential of ESM as a useful tool in addressing pronunciation challenges and enhancing language learning in tourism-focused educational settings. This research aligns with national agendas to improve education quality and supports SDG goals 4 (Quality Education) and 8 (Decent Work and Economic Growth).